Examining Spelling Challenges in English: A Study of Omani Students in Vocational Education - Pankaj B. Vaishnav (JELITA, 2024)
This study investigates the prevalence of spelling errors made by Omani students in Vocational Colleges, particularly focusing on those enrolled in the 'Post Foundation English Program.' The research sample consisted of 100 students (50 male and 50 female), aged 18-20, who were divided equally across five specializations: Electronics, Draftsman, Business Studies, Mechanical, and Electrical. These students, whose first language is Arabic, had studied English as a second language for over 10 years and successfully completed the 'Foundation English Program.' Data collection occurred in three stages. In the first stage, students were assigned to write technical essays in one of four formats: guided, process, argumentative, or informative, each relevant to their specialization. The essays were analyzed for specific spelling errors, focusing on consonant mistakes, silent letters, homophones, and the influence of the students' first language (L1) on their English (L2) spelling. The analysis in the third stage identified common patterns in errors, such as confusion between certain consonants, omissions of silent letters, and incorrect spellings of homophones. The study provides insights into the challenges faced by Arabic-speaking students in mastering English spelling, highlighting the impact of L1 on L2 acquisition. The present study is the result of observation and information gathered over the period of 5 years by a researcher. Integrating contextualized spelling instruction and phonics-based activities into the curriculum, alongside customized remedial practice and specialized workshops can significantly enhance the spelling proficiency of these students.